A The Strategy of Syariah Cooperative Development in Padang Panjang City - Okfi Resti; Asyari Asyari; Winarno Winarno (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Purpose:. The objective of the research are; 1) identifying the aspect of cooperative in the Padang Panjang in order to developthe syariah cooperative 2) identifying the external factor (opportunity and treat) and internal factor (strength and weakness) in developing the Syariah Cooperative in Padang Panjang 3) arrange theprecisealternative strategy in developingSyariah cooperative in Padang Panjang.Design/Method/Approach : The method of primer and secondary data collection were library studies, field observation, questionnaire, and interview. Technique and the tabulation of the data used descriptive analysis, both normatively (according to Syariah rules and state rules), qualitative (describe the profile, explain the EFE, IFE, IE, TOWS, QSPM matrixes) and quantitative (doing the tabulation of calculation on the weighting calculation on EFE, IFE, and IE).Findings: After grouping of strategy by using the I-E matrix, the result of Syariah cooperative developmenton Padang Panjang is gotten which is on the position of Growth strategy, the strategy which is arranged to reach thecondition of capital asset growing, assets, and distribution of cooperative financing. From the matrixes of TOWS and QSP are gotten strategy which are suggested; open the business unit, office to every cooperative, increasing the services quality, supervision and optimize theknowledge enrichment to all of members and management in the Syariah cooperative field.Originality/Values: Syariah cooperative has important roles in increasing the society welfare. However the number and existence of syariah cooperative is still limited.The strategy which will be used to develop the syariah cooperative is necessary.